Iberian Protected Areas Capture Regional Functional, Phylogenetic and Taxonomic Diversity of Most Tetrapod Groups - Llorente-Culebras, Sonia; Molina-Venegas, Rafael; Barbosa, A. Márcia; Carvalho, Silvia B.; Rodríguez, Miguel Á.; Santos, Ana M. C. (Frontiers in Ecology and Evolution, 2021)
Protected areas (PAs) have been created with the purpose of preserving biodiversity, acting as refuges from anthropogenic pressures. Traditionally, PAs have been designed and managed to represent mainly taxonomic diversity, ignoring other diversity facets such as its functional and phylogenetic components. Yet, functional and phylogenetic diversity are respectively connected with species’ roles on ecosystems and evolutionary history held within communities. Here, we focused on the amphibian, reptile, resident breeding bird, and non-flying mammal faunas of the national and natural parks of the Iberian Peninsula, to evaluate whether these PAs are adequately representing regional functional, phylogenetic and taxonomic diversity of each group. Specifically, we computed functional and phylogenetic diversity within each PA, and then compared those values to the ones obtained from a random assembly of species from the regional pool, that was defined as the region encompassing the PA and a neighboring area of 50 km beyond its boundary. We also calculated the proportion of species in each regional pool that were present within the PAs. In general, the functional and phylogenetic diversity of amphibians, reptiles and non-flying mammals found within PAs did not differ significantly from random expectations generated from the species pertaining to the regional pool, although a few PAs showed a higher diversity. In contrast, resident breeding birds presented lower functional and phylogenetic diversity than expected by chance in many of the PAs, which could relate to climatic variables and the habitat specificity of some species. The proportion of species from the regional pools that are present in the PAs was high for amphibians, reptiles and mammals, and slightly lower for birds. These results suggest that the Iberian natural and national parks are effectively capturing the functional, phylogenetic and taxonomic diversity of most tetrapod assemblages present at the regional level. Future studies should identify priority areas to expand the representation of these biodiversity components, and assess potential effects of climate and land-use changes on current patterns.